ASSESSMENT OF TEACHING METHOD PREFERENCES AMONG DENTAL AND MEDICAL STUDENTS - Shaikh, Shoyeb; L Vyas, Megha; Pathak, Shivang (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: The objectives of this study were to evaluate the teaching approach choices among dental and medical college students. Methodology: This survey examines how medical and dental students use their visual, auditory, reading-writing, and kinesthetic senses. It is a descriptive cross-sectional survey. Results: According to VARK, it was found in the current survey that most students chose a single mode of learning (uni modal) – roughly 77% of clinical students and 83% of dentistry students. Tri modal was found to be the least preferred among medical students, with bi modal coming in second with 22% of scientific students and 15% of dentistry students. About 1% of dentistry students were observed using a quad modal method. A-auditory approach was found to be the most popular among medical students, with a median of 2.80, followed by utilizing OK-kinesthetic with a mean of 1.89, and R/W-studying or writing with a mean of 1.65 dentistry college students. A–auditory become the maximum desired approach with a median of two forty, accompanied by okay – kinesthetic with a mean of 2.01 and 1.67for R/W – analyzing or writing Conclusion: According to the study’s findings, kinesthetic mode used most frequently to observe the auditory form of instruction. Both dentistry and medical students were shown to prefer the written style over the visual one. Most of the students selected more than one learning option or had multimodal options.